Aktualisasi Nilai Pendidikan Akhlak dalam Keluarga Menurut QS. An-Nur Ayat 59-60: Studi Komparasi antara Tafsir Al-Misbah dan Tafsir Al-Azhar) - Ifatul Umaroh; Jasminto (LPPM STIT Miftahul Ulum Bangkalan, 2020)
An education is very important in the environment of every individual's life, an education is not only teaching about culture, ethics or morals. The family has an important role in shaping morals, educating and providing good moral examples for their children. The research objectives discussed in this study are: To know the actualization of the Moral Education Value in the Family in QS. An-Nur verses 59-60 according to Tafsir Al-Misbah and Tafsir Al-Azhar. This research is a library research, the data used in this research are books related to research that are relevant to the problems being studied. The results showed that the actualization of moral education in the family according to the perspective of Al-Misbah and Al-Azhar's interpretation of QS. An-Nur [24]: 59-60 is: an order to educate children about adab asking permission in three times for slaves and children who have not reached maturity, namely before the dawn prayer, in the middle of the day after the midday prayer, and after the evening prayer, orders to educate children who are already baligh about adab asking for permission at any time, orders to make cloths at home, advice not to visit at these three times, the relationship between manners asking permission with modern psychiatric developments, dress code that clothes out of the house and clothes in the house.